Anterior Chamber Flare as an Objective and Quantitative Noninvasive Method for Oculopathy in Transthyretin V30M Amyloidosis Patients - João Beirão; Vasco Miranda; Beatriz Pinheiro-Torres; João Coelho; Maria-João Menéres; Pedro Menéres (Journal of Ophthalmology)
Purpose. Assess the aqueous humor flare in transthyretin V30M amyloidosis patients (ATTRV30M). Materials and Methods. This is a retrospective, cross-sectional, noninterventional comparative study including 28 ATTRV30M patients with a unilateral scalloped iris. For comparative analysis, the fellow eye, the nonscalloped iris eye, from each patient was used as control. All patients underwent aqueous humor flare meter and intraocular pressure (IOP) measurements. Results. Mean aqueous humor flare was significantly higher in the eyes with the scalloped iris than the control group with the nonscalloped iris (14.1 ± 2.2 versus 6.5 ± 0.9 pc/ms, respectively). No significant differences in IOP were found in the scalloped iris eyes than those in the nonscalloped iris control group (17.1 ± 0.8 versus 16.8 ± 0.7 mmHg, respectively). No significant correlation was not found between the flare and the IOP value within groups. Conclusions. In this study, aqueous humor flare values in the scalloped iris eyes may be a valid marker for controlling the stage of the oculopathy in ATTRV30M patients.